If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3x + -6 = 9x + 5 Reorder the terms: -6 + 6x + 3x = 9x + 5 Combine like terms: 6x + 3x = 9x -6 + 9x = 9x + 5 Reorder the terms: -6 + 9x = 5 + 9x Add '-9x' to each side of the equation. -6 + 9x + -9x = 5 + 9x + -9x Combine like terms: 9x + -9x = 0 -6 + 0 = 5 + 9x + -9x -6 = 5 + 9x + -9x Combine like terms: 9x + -9x = 0 -6 = 5 + 0 -6 = 5 Solving -6 = 5 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -49+5y+7=2(4y-3)-9 | | k/18=6 | | y^2+4*y=-1 | | 3p+12-4=18 | | 15.57+16.9n=17.8n-6(7.3n+16.71) | | B+9=-9+9b-10b | | 0.96=1.2m | | 4x-29y=27 | | 2(3.14)x=56.52 | | -4(-1-3x)+4=80 | | B+9=-9+9n-10b | | 70.00+3.0x=80+1.00x | | y^2+4*y=-13 | | 8(c-5)+7=4+c-37 | | -7p=133 | | 12w-8=16w+21 | | 9+9s=7s+1 | | -18g=7(-4g+20)+20 | | z-17=20 | | y^2+4*y=-3 | | 4(x+3)-x=x-6 | | X^2+15X=9950 | | -68=1-3(5+3x) | | -4+5b=-39 | | 2(6x-3)=-78 | | 9+2r=4r-1 | | 18p=-16p+5(3p-19) | | 6m=-102 | | 5*tan(x)+3=0 | | 3(w-2)=15 | | 4x=5y-2 | | -4(-1-3k)+4=80 |